Vermiculita reestruturada modificada com nióbio e tungsténio aplicados como material adsorvente - Souto, Cleiton Sarmento (2023)
Methodologies aimed at the treatment of effluents is a branch of research that is constantly the subject of studies in laboratories around the world, this occurs in view of the current scarcity of water resources, associated with the growing number of emerging pollutants found. Among the pollutants found in effluents, dyes can be highlighted, due to the large annual production of these products, combined with the high rate of these residues present in water resources. Several methods are used for the removal of emerging pollutants, in which adsorptive processes can be highlighted. This problem drives research in order to find an effective and low-cost material for the treatment of effluents, among which we can highlight vermiculite, considering that this clay mineral is abundant in Brazil, and due to its properties. Given the above, the present work aims to promote the improvement of the adsorptive capacity of the clay mineral vermiculite, against the methylene blue dye, through changes in its structure. The work consists of the synthesis of clay minerals modified using vermiculite as a precursor solid, which were later characterized by XRD; FTIR; and TG, and applied for dye removal through adsorptive assays. The syntheses of the new solids occurred through the acid restructuring of the vermiculite, and through its modification with niobium and tungsten through the process of precipitation-deposition of metallic species. Through the synthesized matrices, adsorptive tests were performed with variation of time, pH and concentration of the adsorbent. Through the characterization of the solids it was possible to verify the obtaining of new materials with modified structures. Through the adsorptive tests it was possible to prove the improvement of the adsorptive capacity of the restructured solids, being the acidic vermiculite with Niobium the one that presented the best results, presenting a maximum adsorptive capacity of 31.74 mg.g-1. Therefore, through this research, it was verified the improvement of the adsorptive capacity of solids restructured and modified with niobium against the methylene blue dye, being the order of solids with better adsorptive capacity V-W < V-Pura < V-Nb < Va-W < Va-Pura < Va-Nb. The results obtained throughout the research are important in view of the environmental impacts caused by the improper disposal of dyes, in addition to the low cost of the matrix used for the tests.